Deep-UV wavelength-selective photodetectors based on lateral transport in AlGaN/AlN quantum well and dot-in-well structures - Pallabi Pramanik; Sayantani Sen; Chirantan Singha; A. Bhattacharyya; Lin Zhou; David J. Smith (AIP Advances, 2021)
We report on the development of deep-ultraviolet (DUV) wavelength-selective top-illuminated photodetectors based on AlGaN/AlN quantum-dots-in-wells. Structures consisting of 100 AlGaN wells and AlN barriers were grown by plasma-assisted molecular beam epitaxy on sapphire substrates. Interdigitated metal–semiconductor–metal photodetector devices were formed lithographically using indium as the contact metal. The effect of variation of the group III to group V flux ratio and the use of indium as a surfactant on the UV photoresponse were determined. Growth under near-stoichiometric conditions lead to a photocurrent peak in the 210–215 nm range with a peak width of ∼20 nm, with no other additional signatures in the entire UV–visible range. Under excess group III conditions, a second red-shifted peak was observed at ∼225 nm with significantly (up to 10×) higher responsivity. This enhancement was linked to the formation of quantum dots with truncated pyramidal structures with near-uniform size distribution and density of 6 × 1010 cm−2 within the quantum wells. Their formation was attributed to the process of droplet epitaxy. Such photodetectors do not require p-type doping or growth onto UV-transparent substrates and are appropriate for monitoring DUV skin-safe germicidal radiation in the presence of ambient visible light.